Kebijakan Pembubaran Hizbut Tahrir Indonesia: Sebuah Analisis Jejaring Wacana - Syakura, Abdan (Islamic Insights Journal, 2021)
This paper aims to explain the structure of discourse network formed on disbandment policy of Hizbut Tahrir Indonesia (HTI). To expose the network structure is used the actor network theory and discourse coalition. In addition, Discourse Network Analyzer (DNA) and Visone applications are also used as analysis tools. In this study, the network analyzed is the relationship between actors involved in the debate on the policy discourse on the disbandment of HTI. Therefore, to produce the right analysis, the Discourse Network Analysis (DNA) method is used. For the sharper analysis results, also used the concept of discourse and semantic analysis in the process of meaning actor's statement. The discourse analyzed is taken from the widespread online media on the internet. The time period of the discourse taken as the data is May until December 2017. The results of the analysis emerged three discoveries, that is the polarization is out of balance between the supporters and the repellents of the HTI disbandment, the supporters won a glorious victory in the discourse battle with the HTI policy repellent party and supporting the discourse dominance on the repellent party has emerged since the translation process. All three explained that the success of the HTI disbandment policy was also influenced by the strong structure of the discourse networks that emerged in response to the policy.Keywords: HTI’s disbandment; Discourse Network Analysis; Actor-Network Theory; Discourse Coalition; online media.